(untitled) (International Journal of Biology and Chemistry, 2015)
The in vitro culture response of anthers, originating from high yielding and resistance to lodging F1 soft wheat hybrid plants selected under drought conditions, was investigated. The spikes were collected when the microspores were at the mid-uninucleate stage and after 3 days at 40 C for cold pre-treatment, the anthers were cultured in N6 and Gamborg- Eveleg B5 (B5) solid medium. Progeny from 17 different F1 families were used and 9 of them responded to in vitro anther culture and 7 of them produced fertile green plants. Doubled haploid green plants were fertile and produced seeds. Induction of aploid development depends on genotype, stage of male gametophyte development, composition of nutrient media and conditions of cultivation. The effect of the composition of media and different genotypes on wheat anther culture was investigated. From the genotypes produced regenerants, the high yielding genotypes from local breeding collection of wheat produced more albino plants (35.2%) compared to high yielding genotypes from CYMMIT collection (24.92%) ones. Independent of culture medium composition a ratio of doubled haploid/haploid was 4.57:1 and a ratio of haploid/aneuploid was 18.5:1, in particular 81.28 % of green plants were doubled haploid, 17.76% were haploid and the rest (0.96%) were aneuploid